2022
DOI: 10.3390/nu14163263
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Sulforaphane and Alliin in Human Prostate Tissue

Abstract: Diets rich in cruciferous vegetables have been associated with a lower risk of incidence and progression of prostate cancer. Sulforaphane, an isothiocyanate derived from 4-methylsulphinylbutyl glucosinolate (glucoraphanin) that accumulates in certain of these vegetables, notably broccoli, has been implicated in their protective effects. Likewise, the consumption of garlic and its sulphur-containing compounds such as alliin have been associated with a reduction in risk of prostate cancer. In this study, we test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Unfortunately, humans cannot obtain glucoraphanin directly from broccoli seeds. Instead, humans often obtain glucoraphanin from broccoli sprouts or mature broccoli plants, which necessitates broccoli cultivation [ 35 ]. Researchers have also determined that glucoraphanin concentrations are significantly lower in broccoli seedlings than in broccoli seeds [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, humans cannot obtain glucoraphanin directly from broccoli seeds. Instead, humans often obtain glucoraphanin from broccoli sprouts or mature broccoli plants, which necessitates broccoli cultivation [ 35 ]. Researchers have also determined that glucoraphanin concentrations are significantly lower in broccoli seedlings than in broccoli seeds [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism by which CX3CL1 increases alliin levels in the body is not known, in a double-blind trial, it was found that there was no significant difference between the amounts of alliin present in prostate tissue in participants who took alliin supplements for 4 consecutive weeks and those who took a placebo, but the alliin concentrations varied more among different samples within the same group. [ 34 ] Based on these experimental results, we proposed that the alliin levels in prostate tissue are not affected by immediate supplementation. Various biochemical molecules and genetic factors may regulate the accumulation of alliin and metabolism in the prostate.…”
Section: Discussionmentioning
confidence: 94%
“…In many cell and animal models, there have been various studies showing consistency of glucosinolates against prostate cancer. According to Tracey et al [ 48 ], there are three possibles ways of glucosinolates distribution in the prostate gland. First, it may be through hepatic metabolism which results in expression of NF-E2–related factor 2 (‘Nrf2’), which maintains the positive effect of healthy prostate gland tissues.…”
Section: Discussionmentioning
confidence: 99%